Intravaginal progesterone device reinsertion during the early luteal phase affects luteal function and embryo yield in superovulated ewes - Oliveira, Maria Emilia Franco [UNESP]; Caldas, Tarcilla Dutra Barbosa; Rodrigues, Juliana Nascimento Duarte; Vergani, Gabriel Brun [UNESP]; Rangel, Paulo Sergio Cerqueira; Esteves, Luciana Vieira; Souza-Fabjan, Joanna Maria Gonçalves; Brandão, Felipe Zandonadi; Fonseca, Jeferson Ferreira (Elsevier, 2023)
This study checked the efficacy of progesterone (P4) device reinsertion during the early luteal phase on luteal function and embryo yield in superovulated crossbred ewes. Twenty multiparous ewes received an intravaginal P4 device for nine days (D0 to D9) followed by six decreasing doses (25, 25, 15, 15, 10, 10%) of 133 mg pFSH i.m. at 12 h intervals, starting 60 h before P4 device removal. Ewes were naturally mated at 12 h intervals while in estrus. On D13, ewes with viable corpora lutea (CL; n = 19) were equally allocated for receiving their P4 device reinsertion (G-P4; n = 10) or not (G-Control; n = 9). On D17, the P4 device was removed, and all females received the cervical relaxation protocol 16 h to 20 min before non-surgical embryo recovery. CL count and their functionality classification were performed on D13 and D17 by transrectal B-mode and color Doppler ultrasonography (US). Plasma P4 concentrations (ng/mL) of G-P4 ewes increased (P < 0.05) over the days, being greater on D17 (9.2 ± 2.8) than on D9 (1.9 ± 0.7) and D13 (1.6 ± 0.4). The overall CL count per ewe tended to be greater (P = 0.09) in G-P4 compared with G-Control. The occurrence of premature regression of corpora lutea did not differ (P > 0.05) between G-P4 (30.0%) and G-Control (44.4%). The number of ova/embryos recovered was greater (P < 0.05) in G-P4 (11.6 ± 2.9) compared with G-Control (3.7 ± 2.0), respectively. Altogether, the reinsertion of the P4 device for four days after superovulation in ewes promotes greater P4 concentrations, resulting in greater ova/embryos recovered.
Keywords: Early luteal regression; NSER; Progesterone; Sheep; Superovulation